Democratization of book publishing in Nigeria: an analysis of self-publishing from a digital intermediation perspective / Abdulrasheed Adebola Afolabi and Izzal Asnira Zolkepli - Afolabi, Abdulrasheed Adebola; Zolkepli, Izzal Asnira (Faculty of Information Management, 2023)
Communication is a fundamental human right, so everyone who has a story to tell should be able to do so. However, the gatekeeping processes involved in the traditional model of publishing do not make it possible for every voice or story to end up as a book in the hands of readers. This practice is firmly rooted in the “survival of fittest” syndrome which ensures that only manuscripts that assures profits for publishers make it to the book market. As a reaction, marginalized authors at the receiving end of this practice are leveraging on digital technologies to by-pass publishers and connect directly with readers, leading to an increasing rise in self-publishing. While past studies have captured the role of digital technologies in reducing the intermediating role of book publishers between authors and readers, how this intermediation sets the pace for and enhances self-publishing practice in a developing African country like Nigeria has received scant attention. Based on the argument that democratized book publishing promotes literary diversity, this study reviews trends in self-publishing in Nigeria. Analysis reveals that self-publishing has become firmly established as a digital-led publishing model in the country. Recommendations are offered on standardizing self-publishing in the emerging Nigerian digital economy, including the relevance of strategic digital and social media marketing.